A Hybrid Supramolecular Polymeric Hydrogel with Rapid Self‐Healing Property. Issue 11 (4th August 2015) - Chen, Lin; Chen, Hui; Yao, Xuyang; Ma, Xiang; Tian, He
Abstract A hybrid supramolecular polymeric hydrogel is conveniently constructed via host–guest interaction of a host cyclodextrin polymer (poly‐CD) with a guest α‐bromonaphthalene polymer (poly‐BrNp) and mixing with 6‐thio‐β‐cyclodextrin (β‐SH‐CD) modified gold nanoparticles (GPCDs) in aqueous solution. According to the dynamic oscillatory data, the hydrogel exhibits markedly enhanced stiffness compared with the GPCD‐free one (both G′ and G" values are almost twice as high as those of the original GPCD‐free hydrogel) due to the introduction of the inorganic gold nanoparticles. This hybrid supramolecular polymeric hydrogel has a rapid and excellent self‐healing property (only about 1 min, and the G′ and G" of the self‐healed hydrogel almost turned back to their original levels after 1 hour) in air (without adding any solvent or additive).